D-ribose-5-phosphate inactivates YAP and functions as a metabolic checkpoint - Cheng-E Tu; Yong-Feng Liu; Hong-Wei Liu; Chun-Mei Jiao; Quentin Liu; Mien-Chie Hung; Peng Li; Xiang-Bo Wan; Xin-Juan Fan; Yun-Long Wang (Journal of Hematology & Oncology)
Abstract Background Targeting glucose uptake by glucose transporter (GLUT) inhibitors is a therapeutic opportunity, but efforts on GLUT inhibitors have not been successful in the clinic and the underlying mechanism remains unclear. We aim to identify the key metabolic changes responsible for cancer cell survival from glucose limitation and elucidate its mechanism. Methods The level of phosphorylated YAP was analyzed with Western blotting and Phos-tag immunoblotting. Glucose limitation-induced metabolic changes were analyzed using targeted metabolomics (600MRM). The anti-cancer role of metabolite was examined using colony formation assay and APC min/+ mice. Co-immunoprecipitation, LS-MS, qRT-PCR, and immunofluorescence were performed to explore the underlying mechanisms. Results We found that D-Ribose-5-phosphate (D5P), a product of the pentose phosphate pathway connecting glucose metabolism and nucleotide metabolism, functions as a metabolic checkpoint to activate YAP under glucose limitation to promote cancer cell survival. Mechanistically, in glucose-deprived cancer cells, D5P is decreased, which facilitates the interaction between MYH9 and LATS1, resulting in MYH9-mediated LATS1 aggregation, degradation, and further YAP activation. Interestingly, activated YAP further promotes purine nucleoside phosphorylase (PNP)-mediated breakdown of purine nucleoside to restore D5P in a feedback manner. Importantly, D5P synergistically enhances the tumor-suppressive effect of GLUT inhibitors and inhibits cancer progression in mice. Conclusions Our study identifies D5P as a metabolic checkpoint linking glucose limitation stress and YAP activation, indicating that D5P may be a potential anti-cancer metabolite by enhancing glucose limitation sensitivity.